2006
DOI: 10.1007/s00432-006-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of tenascin-C splicing domains in urothelial carcinomas of the urinary bladder

Abstract: In urinary bladder carcinoma a differential expression of Tn-C splicing variants exists in dependence of tumour type, vascularization, and invasive behaviour. Therefore, the detection of different Tn-C splicing domains could be useful for assessment of muscle invasion, tumour surveillance, as well as target structures for antibody based tumour detection and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…TN-C mRNA for the large spliced variant was similarly described to be prevalent in the majority of the thyroid cancer cell lines and thyroid cancers examined (72). The large unspliced TN-C variant containing the A-D domains is increasingly expressed at the invasive fronts of urinary bladder cancers (73), once again suggesting that the unspliced variant that binds Annexin II with a much higher binding affinity, plays an important role in the invasive behavior of cancer cells. A recent review article further describes the role of Tenascin C and its splice variants in cancer (74).…”
Section: B Binding Of Tenascin-c With Annexin Ii: Role In Colorectamentioning
confidence: 90%
“…TN-C mRNA for the large spliced variant was similarly described to be prevalent in the majority of the thyroid cancer cell lines and thyroid cancers examined (72). The large unspliced TN-C variant containing the A-D domains is increasingly expressed at the invasive fronts of urinary bladder cancers (73), once again suggesting that the unspliced variant that binds Annexin II with a much higher binding affinity, plays an important role in the invasive behavior of cancer cells. A recent review article further describes the role of Tenascin C and its splice variants in cancer (74).…”
Section: B Binding Of Tenascin-c With Annexin Ii: Role In Colorectamentioning
confidence: 90%
“…Moreover, the same study identified an association between AD1 and a compact invasion pattern. 120 Similarly, the preferential expression of tenascin-C isoforms containing FNIII repeats B/ D/ AD1/ AD2/ B,D and B,AD1,D is well characterized in breast cancers including ductal carcinoma in situ (DCIS) and is known to occur at the tumor invasion front, and in cancers with elevated risk of metastasis. 49,[121][122][123][124] These isoforms were originally thought to be tumor specific; although a more recent study identified FNIII-AD1 and AD2 expression in the myoepithelium of larger normal ducts in the breast, while also detecting their presence in 34.9% and 23.1% of invasive breast carcinomas respectively.…”
mentioning
confidence: 99%
“…mRNA analysis revealed a higher variability in the B to D region among the investigated carcinomas and a restricted expression of the AD1 to compact invasion type. 51 Although there are reports on the functional importance of Tn-C domains and changes in the Tn-C splicing pattern, 14 the meaning of these findings is not clear. It is known that Annexin II is a ligand of the A-D domains and that the Annexin II / Tn-C interaction may play a role in wound healing.…”
Section: Tenascin-c In Urinary Bladder Carcinoma Invasionmentioning
confidence: 99%